Identifying Significantly Impacted Pathways and Putative Mechanisms with iPathwayGuide. Issue 1 (27th June 2017) - Ahsan, Sidra; Drăghici, Sorin
Abstract: iPathwayGuide is a gene expression analysis tool that provides biological context and inferences from data generated by high‐throughput sequencing. iPathwayGuide utilizes a systems biology approach to identify significantly impacted signaling pathways, Gene Ontology terms, disease processes, predicted microRNAs, and putative mechanisms based on the given differential expression signature. By using a novel analytical approach called Impact Analysis, iPathwayGuide considers the role, position, and relationships of each gene within a pathway, which results in a significant reduction in false positives, as well as a better ability to identify the truly impacted pathways and putative mechanisms that can explain all measured gene expression changes. It is a Web‐based, user‐friendly, interactive tool that does not require prior training in bioinformatics. The protocols in this unit describe how to use iPathwayGuide to analyze a single contrast between two phenotypes (any number of samples), and provide guidance on how to interpret the results obtained from iPathwayGuide. Even though iPathwayGuide has powerful meta‐analysis capabilities, these are not covered in this unit. © 2017 by John Wiley & Sons, Inc.